Questions about Interdisciplinary Terminology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article analyzes and discusses the phenomenon of interdisciplinary terminological problems in scientific literature. The interdisciplinarity of modern science raises the problem of mutual understanding between specialists with basic research and cognitive experience in different scientific fields. One of the sources of difficulties for such mutual understanding is consubstantial terms used in parallel in different professional fields, or in professional and everyday communication. This complexity cannot be overcome only by using specialized terminological dictionaries of individual disciplines, focused only on representatives of one professional field.